Review papersTreatment of cutaneous infections caused by Mycobacterium tuberculosis - Wyrzykowska, Nina; Wyrzykowski, Michał; Żaba, Ryszard; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Tuberculosis is still a very common global problem and it is responsible for more than 4,500 deaths every day. The risk of tubercular infection has been estimated to vary from 1% to 2% in developing countries. In the last years, an increased incidence of tuberculosis has been observed, which in countries with a high socio-economic status may be related to the HIV infection prevalence and population migration. The most frequent form of Mycobacterium tuberculosis infection is tuberculosis of the respiratory system which in Poland accounts for 91.6% of cases. Extra-pulmonary tuberculosis, which includes cutaneous tuberculosis, is rarely observed and its incidence is about 8.4%. With regard to the immunoreactivity or the PPD test and the presence of bacilli, three forms of cutaneous tuberculosis can be distinguished: anergic, reactive and hyperergic. The World Health Organization recommends isoniazid, rifampicin, ethambutol, pyrazinamide and streptomycin as the first-line anti-tuberculosis drugs. This paper is a review of the available present knowledge concerning selected medications, their mechanisms of action and potential adverse effects. Moreover, therapeutic schemes for new tuberculosis patients are also presented.